4
$\begingroup$

Evaluate this indefinite integral. $$I= \int{x\sqrt{4x+1}}dx$$

Let $u=4x+1$
$$\frac{du}{dx}=4\rightarrow{dx=\frac{du}{4}}$$ $$I=\int{x}\sqrt{u}\frac{1}{4}du=\frac{1}{4}\int{x}\sqrt{u}du$$

Then I got stuck at this point.

$\endgroup$
  • 1
    $\begingroup$ As soon as you made your change of variable u = 4 x + 1, x must not appear anymore anywhere. I think that this is why you got stuck. $\endgroup$ – Claude Leibovici Jan 12 '14 at 6:59
  • $\begingroup$ Can you look at the answer down there please and tell me how did he get $ u^{3/2} $ in the third step ? $\endgroup$ – Out Of Bounds Jan 12 '14 at 20:57
3
$\begingroup$

Because we have,$$u = 4x +1 \implies u - 1 = 4x \implies \frac{u - 1}{4} = x$$

Can you do the rest?

$\endgroup$
  • $\begingroup$ $ \frac { 1 }{ 4 } \int { \frac { u-1 }{ 4 } } { u }^{ 1/2 }\quad du\\ \\ \frac { 1 }{ 4 } \int { \frac { 1 }{ 4 } } u-\frac { 1 }{ 4 } { u }^{ 1/2 }\quad du\\ \\ \frac { 1 }{ 16 } \int { u } -\frac { 1 }{ 4 } \int { { u }^{ 1/2 } } \quad du\\ \\ \frac { 1 }{ 16 } \times \frac { 1 }{ 2 } { u }^{ 2 }\quad -\quad \frac { 1 }{ 4 } \times \frac { 2 }{ 3 } { u }^{ 3/2 }\quad +\quad C\\ \\ \frac { 1 }{ 32 } { (4x+1) }^{ 2 }\quad -\quad \frac { 1 }{ 6 } { (4x+1 })^{ 3/2 }\quad +\quad C $ $\endgroup$ – Out Of Bounds Jan 12 '14 at 1:51
  • $\begingroup$ But the answer in the book is $ \frac { 1 }{ 40 } { (4x+1) }^{ 5/2 }\quad -\quad \frac { 1 }{ 24 } { (4x+1 })^{ 3/2 }\quad +\quad C $ $\endgroup$ – Out Of Bounds Jan 12 '14 at 1:52
  • $\begingroup$ @Tennisman: Multiply both terms by $\frac{1}{4}$ in the seind line... $\endgroup$ – DJohnM Jan 12 '14 at 3:26
3
$\begingroup$

$$I= \int{x\sqrt{4x+1}}dx$$

Using Euler Substitution

$$\sqrt{4x+1}=t\iff x=\frac{t^2-1}{4}\iff dx=\frac{t}{2}dt$$

$$\begin{align} I&= \int{x\sqrt{4x+1}}dx\\ &=\int \left(\frac{t^2-1}{4}\right)\frac{t^2}{2}dt\\ &=\frac{t^5}{40}-\frac{t^3}{24}+C\\ &I=\frac{(4x+1)^{5/2}}{40}-\frac{(4x+1)^{3/2}}{24}+C\\ \end{align}$$

$$\int{x\sqrt{4x+1}}dx=\frac{3(4x+1)^{5/2}-5(4x+1)^{3/2}}{120}+C$$

$\endgroup$
2
$\begingroup$

$$I = \int x \sqrt{4x+1} \ dx$$

let $u$ = $4x+1$

$x = \frac{u-1}{4}$

$ \text{d}x = \frac{\text{d}u}{4}$

$$ \begin{align} I &= \int x \sqrt{4x+1} \ \text{d}x \\ &= \int \left(\frac{u-1}{4} \right) u^{1/2} \frac{\text{d}u}{4} \\ &= \frac{1}{16}\int u^{3/2}\text{d}u - \frac{1}{16}\int u^{1/2}\text{d}u \\ &= \frac{1}{16}\frac{u^{5/2}}{5/2} - \frac{1}{16}\frac{u^{3/2}}{3/2} + \text{C} \\ &= \frac{1}{40}u^{5/2} - \frac{1}{24}u^{3/2} + \text{C} \\ &= \frac{1}{40}(4x+1)^{5/2} - \frac{1}{24}(4x+1)^{3/2} + \text{C} \end{align} $$

$\endgroup$
  • $\begingroup$ How did you get $ u^{3/2} $ in the third step ? $\endgroup$ – Out Of Bounds Jan 12 '14 at 2:55
  • $\begingroup$ @Tennisman.Develop what is inside parentheses : u times u^(1/2) = u^(3/2) $\endgroup$ – Claude Leibovici Jan 13 '14 at 7:22
1
$\begingroup$

$$\begin{align} I &= \int \left(x*\sqrt{4x + 1}\right)dx \\ u &= 4x + 1 \\ (4x + 1)dx &= du \\ \left(\frac{d}{dx}(4x + 1)\right)dx &= du \\ \left(\frac{d}{dx}(4x) + \frac{d}{dx}(1) \right)dx &= du \\ \left(\frac{d}{dx}(4x) + 0 \right)dx &= du \\ \left(4*\frac{d}{dx}(x) + 0\right)dx &= du \\ \left(4*\frac{dx}{dx} + 0\right)dx &= du \\ (4 + 0)dx &= du \\ (4)dx &= du \\ dx &= \left(\frac{1}{4}\right)du \\ I &= \int\left(x*\sqrt{u}*\frac{1}{4}\right)du \\ &= \frac{1}{4}*\int\left(x*\sqrt{u}\right)du \\ u &= 4x + 1 \\ 4x + 1 &= u \\ 4x &= u - 1 \\ x &= \left(\frac{u - 1}{4}\right) \\ I &= \frac{1}{4}*\int\left(\frac{(u - 1)}{4}*\sqrt{u}\right)du \\ &= \frac{1}{4}*\frac{1}{4}*\int\left((u - 1)*\sqrt{u}\right)du \\ &= \frac{1}{16}*\int\left((u - 1)*\sqrt{u}\right)du \\ &= \frac{1}{16}*\int\left(\sqrt{u}*u - \sqrt{u}\right)du \\ &= \frac{1}{16}*\int\left(u^{\frac{1}{2}}*u^1 - u^{\frac{1}{2}}\right)du \\ &= \frac{1}{16}*\int\left(u^{(\frac{1}{2} + 1)} - u^{\frac{1}{2}}\right)du \\ &= \frac{1}{16}*\int\left(u^{(\frac{1}{2} + \frac{2}{2})} - u^{\frac{1}{2}}\right)du \\ &= \frac{1}{16}*\int\left(u^{\frac{3}{2}} - u^{\frac{1}{2}}\right)du \\ &= \frac{1}{16}*\left(\int\left(u^{\frac{3}{2}}\right)du - \int\left(u^{\frac{1}{2}}\right)du\right) \\ &= \frac{1}{16}*\left(\int\left(u^{\frac{3}{2}}\right)du - \frac{1}{\left(\frac{1}{2} + 1 \right)}*u^{\left(\frac{1}{2} + 1\right)}\right)\\ &= \frac{1}{16}*\left(\int\left(u^{\frac{3}{2}}\right)du - \frac{1}{\left(\frac{1}{2} + \frac{2}{2}\right)}*u^{\left(\frac{1}{2} + \frac{2}{2}\right)}\right) \\ &= \frac{1}{16}*\left(\int\left(u^{\frac{3}{2}}\right)du - \frac{1}{\left(\frac{3}{2} \right)}*u^{\frac{3}{2}}\right) \\ &= \frac{1}{16}*\left(\int\left(u^{\frac{3}{2}}\right)du - \frac{2}{3}*u^{\frac{3}{2}}\right) \\ &= \frac{1}{16}*\left(\frac{1}{\left(\frac{3}{2} + 1\right)}*u^{\left(\frac{3}{2} + 1\right)} - \frac{2}{3}*u^{\frac{3}{2}}\right) \\ &= \frac{1}{16}*\left(\frac{1}{\left(\frac{3}{2} + \frac{2}{2}\right)}*u^{\left(\frac{3}{2} + \frac{2}{2}\right)} - \frac{2}{3}*u^{\frac{3}{2}}\right) \\ &= \frac{1}{16}*\left(\frac{1}{\left(\frac{5}{2}\right)}*u^{\frac{5}{2}} - \frac{2}{3}*u^{\frac{3}{2}}\right) \\ &= \frac{1}{16}*\left(\frac{2}{5}*u^{\frac{5}{2}} - \frac{2}{3}*u^{\frac{3}{2}}\right) \\ &= \frac{1}{16}*\frac{2}{5}*u^{\frac{5}{2}} - \frac{1}{16}*\frac{2}{3}*u^{\frac{3}{2}} \\ &= \frac{2}{80}*u^{\frac{5}{2}} - \frac{2}{48}*u^{\frac{3}{2}} \\ &= \frac{1}{40}*u^{\frac{5}{2}} - \frac{1}{24}*u^{\frac{3}{2}} \\ u &= 4x + 1 \\ I &= \frac{1}{40}*\left(4x + 1\right)^{\frac{5}{2}} - \frac{1}{24}*\left(4x + 1\right)^{\frac{3}{2}} \\ I &= \bf\left[\frac{1}{40}*\left(4x + 1\right)^{\frac{5}{2}} - \frac{1}{24}*\left(4x + 1\right)^{\frac{3}{2}} + C \right] \\ \end{align}$$

#

Can anyone explain how wolfram gets this result?:

$$\frac{1}{60}*\left(4x+1\right)^{\frac{3}{2}}*\left(6x-1\right) + C$$

$\endgroup$
  • $\begingroup$ $\displaystyle \frac{1}{40}(4x+1)^{2.5}-\frac{1}{24}(4x+1)^{1.5}=\frac{1}{120}(4x+1)^{1.5} \left[3(4x+1)-5 \right]=\frac{1}{60}(4x+1)^{1.5}(6x-1)$ $\endgroup$ – Galc127 Nov 23 '14 at 9:37
0
$\begingroup$

$\newcommand{\angles}[1]{\left\langle\, #1 \,\right\rangle} \newcommand{\braces}[1]{\left\lbrace\, #1 \,\right\rbrace} \newcommand{\bracks}[1]{\left\lbrack\, #1 \,\right\rbrack} \newcommand{\ceil}[1]{\,\left\lceil\, #1 \,\right\rceil\,} \newcommand{\dd}{{\rm d}} \newcommand{\ds}[1]{\displaystyle{#1}} \newcommand{\expo}[1]{\,{\rm e}^{#1}\,} \newcommand{\fermi}{\,{\rm f}} \newcommand{\floor}[1]{\,\left\lfloor #1 \right\rfloor\,} \newcommand{\half}{{1 \over 2}} \newcommand{\ic}{{\rm i}} \newcommand{\iff}{\Longleftrightarrow} \newcommand{\imp}{\Longrightarrow} \newcommand{\pars}[1]{\left(\, #1 \,\right)} \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\pp}{{\cal P}} \newcommand{\root}[2][]{\,\sqrt[#1]{\vphantom{\large A}\,#2\,}\,} \newcommand{\sech}{\,{\rm sech}} \newcommand{\sgn}{\,{\rm sgn}} \newcommand{\totald}[3][]{\frac{{\rm d}^{#1} #2}{{\rm d} #3^{#1}}} \newcommand{\verts}[1]{\left\vert\, #1 \,\right\vert}$ \begin{align}&\color{#66f}{\large\int x\root{4x + 1}\,\dd x} ={1 \over 4}\bracks{% \int\pars{4x + 1}^{3/2}\,\dd x - \int\pars{4x + 1}^{1/2}\,\dd x} \\[3mm]&={1 \over 4}\bracks{{\pars{4x + 1}^{5/2} \over 4\times 5/2} -{\pars{4x + 1}^{3/2} \over 4\times 3/2}} =\color{#66f}{\large{3\pars{4x + 1}^{5/2} - 5\pars{4x + 1}^{3/2} \over 120}} + \pars{~\mbox{a constant}~} \end{align}

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.